PENDIDIKAN AKHLAK BERWAWASAN INTEGRATIF INKLUSIF - Syifaqurrohman, M (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2019)
Integrative-inclusive morality education can be interpreted as a formulation of a moral education process that is carried out broadly and holistically. Moral education materials can synergize with all subjects, can synergize with school culture, estrakulikuler activities and synergy with the community. It is said that the integrative scientific structure does not mean that the various sciences are merged into an identical form of science, but rather the character, style, and nature of the science are integrated in the unity of the spiritual material dimensions, revelation, general science of religion, physical and spiritual world, and the world hereafter